NEUROPROTECTIVE AND ANTIOXIDANT ACTIVITIES OF AQUEOUS EXTRACT MORINGA OLEIFERA LEAVES - PURWONINGSIH, EMNI; AROZAL, WAWAIMULI; LEE, HEE J.; MUNIM, ABDUL (International Journal of Applied Pharmaceutics, 2022)
Objective: To investigate the neuroprotective and antioxidant effects of leaves aqueous extract Moringa oleifera (MW) in chronic stress mouse models. Methods: Water immersion and stress restraint for 16 d to obtain a chronic stress model animal. Moringa extract flour dissolved in Aquades, dose 800 mg/kg for 23 d, for chronic Stress+MOW group. Fluoxetine in aquades at a dose of 18 mg/kg BW for 23 d for chronic stress group+Fluoxetine. Aquades were given to normal mice (group N), and mice under chronic stress conditions (chronic stress control group). Furthermore, measure behavioral abnormalities by testing depressive behavior and oxidative stress parameters such as anxiety, Brain-derived neurotrophic factors (BDNF). Results: Moringa oleifera water extract administration can improve behavioral disorders caused by stress by decreasing immobility time on the Force swim test, increasing time in the middle area, and increasing the number of returns to center areas on the Open field test. When chronically stressed mice were given fluoxetine and MOW, their MDA levels (p=0.008 and 0.041, respectively) and SOD activity (p=0.001 and 0.004) decreased significantly compared to the chronic stress control group. In contrast, Catalase activity increased significantly in chronically stressed mice given fluoxetine and MOW compared to the chronic stress control group (p=0.010 and 0.013). Administration of fluoxetine and MOW may increase the expression of mRNA BDNF compared to the chronic stress control group (p=0.000 and 0.013). Conclusion: The study found that MOW can improve behavioral abnormalities, namely anxiety and depression behavior caused by chronic stress exposure, through antioxidant pathways and oxidant systems, and also BDNF